Restoration of fresh cat ovarian tissue function by autografting to subcutaneous tissue: A pilot study - Leonel, Ellen C.R. [UNESP]; Vilela, Janice M.V.; Paiva, Raísa E.G.; Jivago, José L.P.R.; Amaral, Rodrigo S.; Lucci, Carolina M. (Elsevier, 2018)
Ovarian tissue transplantation could be a valuable technique for the preservation of endangered animals. The domestic cat affords an adequate experimental model for studies aimed at wild felids due to its phylogenetic similarity. Thus, this pilot study evaluated the efficacy of cat ovarian tissue autotransplantation to a peripheral site. Three adult queens were submitted to ovariohysterectomy. The ovaries were fragmented into eight pieces; two were fixed as a control and six were transplanted to subcutaneous tissue of the dorsal neck. Grafts were monitored weekly by ultrasound and fecal samples collected daily in order to monitor estradiol levels. Grafts were recovered on Days: 7, 14, 28, 49 and 63 post-transplantation for histological analyses. One graft was maintained in one animal for 8 months. A total of 2466 ovarian follicles were analyzed: 1406 primordial and 1060 growing follicles. All animals presented antral follicles in one or more of the grafts. The percentage of morphologically normal primordial follicles was always higher than 80%, except for Day 7 transplants. Although the proportion of growing follicles increased after transplantation, there was a general decrease in the percentage of morphologically normal growing follicles from Day 7 onwards. All animals demonstrated at least three estradiol peaks during the 63-day period, and one animal exhibited estrous behaviour on three occasions. Hormonal peaks directly correlated with the visualization of antral follicles (by ultrasound and/or histology) and the observation of estrous behaviour. Long-term results on one female showed the concentration of 37.8 pg/mL of serum estradiol on Day 233 post-grafting and the female exhibited estrous behaviour on several occasions. This graft showed one antral follicle, one luteinized follicle and two preantral follicles. In conclusion, cat ovary autotransplantation to the subcutaneous tissue restored ovarian function, with hormone production and antral follicle development, over both short and long term periods. This could be a valuable technique in the evaluation of ovarian cryopreservation methods in felids. Once the technique is shown successful, it may be applied in allografts or xenografts between different feline species.
Keywords: Antral follicle; Fecal steroids; Ovarian transplant; Primordial follicle activation; Steroidogenesis